The impact of voluntary corporate disclosure on tax planning: An applied analytical research of a sample of Iraqi private joint-stock companies (Journal of Accounting and Financial Studies ( JAFS ), 2020)
In recent years, the attention of researchers, governments and international non-governmental organizations has focused on the aggressive practices adopted by companies with the aim of evading the tax burden or from paying the tax obligations imposed on them by law, as the results of these practices are negatively affected by tax revenues. And that companies are part of the society in which they work, and they have rights and obligations, including paying taxes. The research community is the Iraqi private shareholding companies, and the research sample was 4 companies within the private sector and in the field and finance - banking, insurance, industrial and service, which are Ashur Bank, Al-Ahlia Insurance Company, Baghdad Soft Drinks Company and Asia Cell Company. The research aimed to measure the effect of the voluntary disclosure of companies on tax evasion in the companies of the research sample and for the period from 2011 to 2015 through the results of analyzing the level of practice of the searched companies for the voluntary disclosure. The absence of a trace of voluntary disclosure in tax evasion and the research summarized the variation and difference in the rates of voluntary disclosure for companies between sectors. There is no specific or converging level, which means that each company has its own unique policy, culture and awareness of adopting and practicing optional disclosure regardless of the sector in which it operates. And Iraqi private shareholding companies, based on the results of the analysis of the financial reports of the companies, the research sample practiced tax evasion at different rates The most important thing is the adoption of the optional disclosure measurement model proposed in this research as a basis for measuring the optional disclosure, as it is a measure that includes many financial, insurance, industrial and service sectors and activating the role of the supervisory and supervisory authorities, in the forefront of which is the tax administration represented by the General Tax Authority and reducing the opportunities and volume of manipulation in financial reports and imposing penalties Strict and deterrent against those who violate the tax law and infringe on it and try to present misleading financial data by enacting many judicial rulings and high fines